2017
DOI: 10.3389/fphar.2017.00580
|View full text |Cite
|
Sign up to set email alerts
|

Altered CYP19A1 and CYP3A4 Activities Due to Mutations A115V, T142A, Q153R and P284L in the Human P450 Oxidoreductase

Abstract: All cytochromes P450s in the endoplasmic reticulum rely on P450 oxidoreductase (POR) for their catalytic activities. Mutations in POR cause metabolic disorders of steroid hormone biosynthesis and affect certain drug metabolizing P450 activities. We studied mutations A115V, T142A, Q153R identified in the flavin mononucleotide (FMN) binding domain of POR that interacts with partner proteins and P284L located in the hinge region that is required for flexibility and domain movements in POR. Human wild-type (WT) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 51 publications
5
53
0
Order By: Relevance
“…However, prior to the present study, none of the mutations located at the FAD domain reported to date has enhanced activity, as documented here for mutants 1‐014 and 1‐053, which supported CYP2C9 and CYP2A6 activity respectively with NADPH more efficiently than the wt (Figs and respectively). A mutation at the FMN domain, Q153R, led to enhanced activity up to 4‐fold with CYP19A1, CYP1A2, CYP2C19, CYP2D6 and CYP3A4 . Similar to our results, the benefit of this mutation was dependent on the P450 form studied and decreased activity was seen with some P450s compared to the wt.…”
Section: Resultssupporting
confidence: 88%
“…However, prior to the present study, none of the mutations located at the FAD domain reported to date has enhanced activity, as documented here for mutants 1‐014 and 1‐053, which supported CYP2C9 and CYP2A6 activity respectively with NADPH more efficiently than the wt (Figs and respectively). A mutation at the FMN domain, Q153R, led to enhanced activity up to 4‐fold with CYP19A1, CYP1A2, CYP2C19, CYP2D6 and CYP3A4 . Similar to our results, the benefit of this mutation was dependent on the P450 form studied and decreased activity was seen with some P450s compared to the wt.…”
Section: Resultssupporting
confidence: 88%
“…The CYP19A1 deficiency is linked to genetic disorders of estrogen biosynthesis in women and developmental disorders in men [19,31,46,85,86]. Previously we have tested the CYP19A1 variants (R264C and R26H) and POR genetic variants in separate studies that focused on individual genes [59,64,70]. Cytochromes P450 and P450 reductase have a large number of genetic variations and, therefore, many individuals may harbor variations in P450 reductase as well as P450 genes that may alter the enzymatic activities of cytochromes P450 [87].…”
Section: Discussionmentioning
confidence: 99%
“…The biosynthesis of estrogens requires the aromatase activity of CYP19A1, which is reliant on POR. Figure adapted from our previous publication by [64]. B: Electron transfer from NADPH to CYP19A1 is carried out via POR through reduced FAD and FMN.…”
Section: Figure 1: Steroid Hormone Biosynthesis and Role Of Por Amentioning
confidence: 99%
See 2 more Smart Citations